Socio-economic status over the life course and obesity: Systematic review and meta-analysis. - Suzy Newton; Dejana Braithwaite; Tomi F Akinyemiju (PLoS ONE)
Background The purpose of this review was to summarize the published literature on the association of childhood, adulthood and life course socio-economic status (SES) with obesity between January 1990 and June 2015. Methods The major medical electronic databases were searched to identify studies that examined SES over the life-course in relation to obesity. A total of 219 studies were identified through the initial search, and 35 qualified for full review. Of these, 14 publications met our inclusion criteria for the meta-analysis, all from developed or upper-middle income countries. Results There was a consistent association between lower life course SES and obesity among women (summary OR: 1.35, 95% CI: 1.04, 1.76), but not among men (summary OR: 0.92, 95% CI: 0.60, 1.40). Overall, mean BMI was higher among individuals with lower life course SES compared with those with higher life course SES (summary mean BMI difference: 0.65, 95% CI: 0.59, 0.71). Mean waist circumference (WC) was higher among women with lower life course SES compared with those with higher life course SES (summary mean WC: 4.67, 95% CI: 4.15, 5.20), but lower among men (summary mean WC difference: -0.10, 95% CI: -0.11, -0.08). Conclusion The inverse relationship between life course SES and obesity among women was consistent, based mostly on studies in developed countries. Nevertheless, critical information gaps remain in relation to the impact of childhood and life course SES on obesity in developing countries.